Sate Renteng Sebagai Daya Tarik Wisata Budaya di Desa Wisata Baha: Perspektif Kajian Budaya - Dewa Putu Oka Prasiasa; Dewa Ayu Diyah Sri Widari (Mudra Jurnal Seni Budaya, 2022)
In the Hindu community in Bali, it is known that there are various kinds of satay that are used for complete ceremonies. One of the many satays is sate renteng or jerimpen from the Baha Tourism Village which has a unique value. Therefore, this study examines sate renteng or jerimpen in order to find the aesthetic value as well as the form, function, and meaning of sate renteng or jerimpen in the cultural life of the Baha Tourism Village community. This study found that the form of sate renteng or jerimpen at upakara in the Baha Tourism Village was formed with a banana tree trunk, on top of which satay was placed consisting of satay lembat, satay katik 3, satay katik 4, satay katik 5, satay katik 7, pipid, apit surang, kepuh stump, squeeze, penyeneng, chakra, umbul-umbul, pajeng, garuda, and kekuwung. As a complement to the offerings, you can get tumpeng 7, slashes, jerimpen jaja and gebogan. The function of sate renteng or jerimpen is as a means to ask for or get happiness and success, to be kept away from all dangers, and to always be successful in life. While the meanings contained in the making of sate renteng or jerimpen are the meaning of Tattwa Education (philosophy), Moral Education (ethics), and Ceremonial Education (ritual).